Representation of race, class and morality in peruvian television. A social analysis of “Magaly TeVe” and “Al fondo hay sitio” - Sánchez Dávila, Mario (2013)
This article proposes to analyze the representation of race, class and moral in television phenomena “Magaly TeVe” and “Al fondo hay sitio” from an anthropological glance of the television, and understanding their communicative, discursive and social dimensions. On one hand, after analyzing the discourse of “Magaly TeVe”, it was easy to see that the why and how the success of the communication strategy for this television phenomenon closely imposes moral and socially shared codes, and a configured mode of organization, relationship and interaction already validated in our social fabric. On the other hand, after analyzing the discourse of “Al fondo hay sitio”, it was easy to see that we have confused, naively, inclusion with redemption within a framework of convergence space-time of two contradictory cultural codes that permanently relate and interact from guidelines of race and class that function as semantic cores that shape, on the other hand, a determined social relationship and interaction of power and symbolic violence between his characters.